The ethics of caring and its application in nursing profession - García Moyano, Loreto (Acta Bioethica, 2015)
This article has as aim to analyze the usefulness of the ethics of caring in nursing profession. For this it will be necessary to define the concepts of “caring” and “ethics of caring” and analyze the possible practical application of ethics of caring in the nursing field of Spain. The analytic-synthetic method, bibliography review, comprehensive reading, personal reflection, definition of concepts and comparative method were used.